2018
DOI: 10.5539/enrr.v8n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Health Threats Associated with Drainage from a Coastal Urban Watershed

Abstract: The project goal was to determine if stormwater runoff and the legacy effects of leaking underground storage tanks (UST) posed an environmental health threat along an urban stream, Town Creek (TC). Baseflow and stormflow samples were collected from TC between March and October 2016 for physical and chemical characterization and E. coli analyses. Groundwater seeps and wells near the banks of TC were also sampled for E. coli and benzene analyses. Stormflow concentrations of E. coli were significantly (p < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Average annual rainfall in the watershed is 126 cm, with precipitation being higher during the summer months. Previous monitoring indicated that Town Creek was known to have elevated E. coli concentrations that varied based on flow conditions (Humphrey et al, 2018). Town Creek discharges to the Tar River, which is classified as secondary recreation waters at this location because water‐based recreation, including kayaking and fishing, are popular in the area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Average annual rainfall in the watershed is 126 cm, with precipitation being higher during the summer months. Previous monitoring indicated that Town Creek was known to have elevated E. coli concentrations that varied based on flow conditions (Humphrey et al, 2018). Town Creek discharges to the Tar River, which is classified as secondary recreation waters at this location because water‐based recreation, including kayaking and fishing, are popular in the area.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the documented relationship between flow and E. coli concentrations (Humphrey et al, 2018), breaking the data into base flow and storm flow subsets would have been logical for this study. Flow data was not available in this stream during the study period; hence, it could not be used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeps can bestow water quality services by contributing to food webs (Williams ) and by attenuation of contaminants (O’Driscoll and DeWalle ). However, seeps can also act as net contaminant sources (Williams et al , ; Humphrey et al ). From a water quality perspective, seeps can provide portholes to observe groundwater quality.…”
mentioning
confidence: 99%
“…Although seeps may make up a relatively small extent of a catchment, they are important components of the watershed ecosystem because of their capability to translate groundwater contaminants to streams and wetlands (Williams et al ; Humphrey et al ) and act as nutrient cycling (McClain et al ) and ecological diversity hotpots (Stevens and Meretsky ; Griebler and Avramov ; Williams ). Springs and seeps are key aquatic habitats because they exert a broad influence on regional ecosystem structure, function, and evolutionary processes (Stevens and Meretsky ).…”
mentioning
confidence: 99%